The coffee rust crises in Colombia and Central America (2008-2013): impacts, plausible causes and proposed solutions - Avelino, Jacques; Cristancho, Marco; Georgiou, Selena; Imbach, Pablo A.; Aguilar, Lorena; Bornemann, Gustavo; Läderach, Peter; Anzueto, Francisco; Hruska, Allan J.; Morales, Carmen (2015)
Food Security. Volumen 7, número 2 (Abril 2015), páginas 303-321